Trauma‐informed qualitative research: Some methodological and practical considerations - Isobel, Sophie (International journal of mental health nursing, 2021)
Mental health nurses who engage in research are likely to undertake research on sensitive topics, related to experiences of illness, care delivery and treatment. With recognition of the high prevalence of trauma in the lives of people who interact with mental health services, it is likely that many research participants will have experienced trauma in their lives and that while this may not be the focus of the research, sensitivity and awareness are required. Reference to ‘trauma‐informed’ approaches in research design and practice is emerging in fields such as trauma‐focused research and social sciences; however, it has not yet been applied to nurses. Trauma‐informed approaches can build upon existing ethical and methodological frameworks to inform how mental health nurses go about qualitative research and what they need to consider when doing so. This discursive paper explores some of the implications of awareness and sensitivity to trauma for research undertaken by mental health nurses, including practical and methodological considerations. Recommendations include training and structural supports for nurse researchers, collaborative research designs, consideration of the environments where research occurs, awareness of approaches to distress and inclusion of trauma sensitivity within research policies, frameworks and leadership, alongside vigilance to interpersonal approach and the establishment and protection of psychological safety throughout. Continuing to undertake research on topics, and with people, where trauma is present, is essential to ensure ongoing awareness. Many of the existing skills held by mental health nurses can also support research to be undertaken in trauma‐informed ways.